PLA-based biocomposites and bionanocomposites in the biomedical and healthcare applications - Kuram, Emel (Elsevier, 2024)
The selection of materials for employing the regeneration of degenerated and traumatized tissues is a very challenging task. Recently, researchers have started to use biopolymers or biocomposites in biomedical and healthcare applications because they are nonallergenic and noncorrosive. These materials are also compatible with modern diagnostic methods. Poly(lactic acid) (PLA) possesses promising properties such as biocompatibility, biodegradability, processability, and strength, which make it suitable for drug carriers, implants, orthopedic applications, and scaffolds. This chapter has reported recent advances in the area of PLA and its biocomposites for potential biomedical and healthcare applications. To this aim, detailed examples of PLA and its biocomposites in biomedical and healthcare applications are presented from the scientific literature studies. PLA-based biocomposites in the form of implants and medical devices have the potential to allow replacement and/or regeneration of degenerated or traumatized organs or tissues, aiding healing and correcting abnormalities, thus improving patients' quality of life. © 2025 Elsevier B.V., All rights reserved.
Keywords: Biocomposite; Biomedical applications; Bionanocomposite; Healthcare applications; PLA